Effect of diazepam on kidney function and histological structure of white rat’s kidney - Putu Gede Martha Setiawan; Woro Anindito Sri Tunjung; Luthfi Nurhidayat (The East Java Biological Society, 2016)
The use of NAPZA (Narcotics, Alcohol, Psychotropic, and other addictive substances) in Indonesia keeps increasing. One type of frequently used NAPZAs is diazepam. Diazepam is a kind of sedative-hypnotics drug which belongs to benzodiazepine. The objective of this study was to determine kidney function by examining the level of urine ureum and creatinine also histological structure in rat after treated with diazepam. Rats were divided into one control group and three diazepam treatment groups which were solvent control (PEG 1%), treatment I (62.25 mg/kg BW), treatment II (83 mg/kg BW), and treatment III (124.5 mg/kg BW) of diazepam. These doses were based on LD50 in human. Rat urine was taken on the D0, D7, D14, D21, and D28. The ureum level was examined by ureumse-GLDH method and the creatinine level was analyzed by Jaffe method. The histological section was made by paraffin method with Hematoxylin and Eosin (HE) staining. Results showed that diazepam given to rat for 28 days led the in-crease of urine ureum and creatinine levels compare to control group. Furthermore, histological damages of the kidney also detected including cellular injuries, both reversible and irreversible injuries, congestion, hemorrhage, and glomerular damage. In conclusion, the use of diazepam for 28 days affected kidney function in rat.